Bacteriuria screening by use of acridine orange-stained smears. - Hoff, R G (1985)
Acridine orange (AO)-stained smears of 1,042 urine specimens were examined for the presence of bacteria and compared with quantitative culture results. The detection of one or more organisms per three AO fields at X200 magnification was noted in 161 of 162 and 193 of 195 urine specimens that grew greater than 10(5) and 10(4) CFU/ml, respectively, of a clinically relevant organism. However, a high number of false-positive AO smears (356 and 324, respectively) was observed among urines that failed to grow organisms at 10(5) and 10(4) CFU/ml. Sensitivity, specificity, and positive and negative predictive values of AO smears were 99, 58, 26, and 99%, respectively, for cultures of greater than or equal to 10(5) CFU/ml and 98, 59, 32, and 99%, respectively for cultures of greater than or equal to 10(4) CFU/ml. Despite the poor specificity of the AO smear, the very high negative predictive value would allow for the ruling out of bacteriuria defined at 10(4) CFU/ml and would eliminate the need for culture of ca. 50% of the urine specimens in this study. Employment of the rapid, inexpensive AO procedure only as a means to eliminate specimens for culture would allow significant cost savings and permit the laboratory to send out a large number of potentially negative or low-count urine results within a short time of specimen receipt.